Solvent extraction and identification of active anticariogenic metabolites in Piper cubeba L. through 1H NMR-based metabolomics approach - Raja Mazlan, Raja Nur Asila; Rukayadi, Yaya; Maulidiani, M.; Ismail, Intan Safinar (MDPI, 2018)
The aim of this study was to determine the effects of different solvents for extraction, liquid⁻liquid partition, and concentrations of extracts and fractions of Piper cubeba L. on anticariogenic; antibacterial and anti-inflammatory activity against oral bacteria. Furthermore, ¹H-Nuclear Magnetic Resonance (NMR) coupled with multivariate data analysis (MVDA) was applied to discriminate between the extracts and fractions and examine the metabolites that correlate to the bioactivities. All tested bacteria were susceptible to Piper cubeba L. extracts and fractions. Different solvents extraction, liquid⁻liquid partition and concentrations of extracts and fractions have partially influenced the antibacterial activity. MTT assay showed that P. cubeba L. extracts and fractions were not toxic to RAW 264.7 cells at selected concentrations. Anti-inflammatory activity evaluated by nitric oxide (NO) production in lipopolysaccharide (LPS) stimulated cells showed a reduction in NO production in cells treated with P. cubeba L. extracts and fractions, compared to those without treatment. Twelve putative metabolites have been identified, which are (1) cubebin, (2) yatein, (3) hinokinin, (4) dihydrocubebin, (5) dihydroclusin, (6) cubebinin, (7) magnosalin, (8) p-cymene, (9) piperidine, (10) cubebol, (11) d-germacrene and (12) ledol. Different extraction and liquid⁻liquid partition solvents caused separation in principal component analysis (PCA) models. The partial least squares (PLS) models showed that higher anticariogenic activity was related more to the polar solvents, despite some of the active metabolites also present in the non-polar solvents. Hence, P. cubeba L. extracts and fractions exhibited antibacterial and anti-inflammatory activity and have potential to be developed as the anticariogenic agent.